Empowering Women Through Equal Land Rights : Experimental Evidence From Rural Uganda - Cherchi, Ludovica; Goldstein, Markus; Habyarimana, James; Montalvao, Joao; O'Sullivan, Michael; Udry, Chris; Gruver, Ariel (World Bank, Washington, DC, 2019)
Traditional customary land tenure systems often limit women’s land rights in Sub-Saharan Africa.In an ongoing experiment in rural Uganda, we offered households fully-subsidized land titles and basic information about the benefits of land titling.Providing additional gender information and making the offer conditional on female co-tilting raised the take up of joint titles to about 76 percent and 89 percent, respectively, without dampening overall demand for titling.